Online social networking usage pattern of UPV students. - Gatumbato, Praise T.; Lim, Caressa Leanne V.
The study was undertaken to know the pattern of online social networking usage among UPV students. It generally aims to identify the online social networking usage pattern among UPV students by (1) describing the profile of high school and college students who engage in online social networking; (2) determining the relationship between sex and online social networking usage of UPV students; (3) determining the relationship between age and online social networking usage of UPV students; (4)determining the relationship between educational level and online social networking usage of UPV students. The researchers used the stratified random sampling method with replacement wherein the population is divided into two strata by high school and college students. The data was gathered by using the structured questionnaire and analyzed using simple frequency counts and percentages. The researchers also used the chi-square test for independence as statistical tool in testing the hypothesis., The study found that majority of the respondents claimed that they access the internet in the internet cafes and that they first know about online social networking through their friends. They are aware of what online social networking is. All of them are members of several online social networking sites and majority of them say that they are members of this sites for almost four years already. Moreover, they also avail different features offered by these sites such as testimonial and messaging wherein majority of them are satisfied with these features. On the other hand, it was shown that both male and female students from ages 13-22 tend to use online social networking sites less frequently. Generally, high school students tend to use online social networking sites more frequently for a short duration than college students who use online social networking less frequently for a short duration. The researchers concluded that the frequency and duration of online social networking of UPV students are independent of the sex and age of the students. The educational level of the students, on the other hand, influenced the frequency of using online social networking. As for the recommendation, the researchers suggested to conduct a parallel study of online social networking usage to other schools and universities. Furthermore, the researchers would like to recommend expanding the number of respondents for a more significant result. Also, for those interested to pursue the same interest, the researchers recommend that they use variables other than what the researchers used to explore the study area more.
Research Paper (Undergraduate, Bachelor of Arts in Social Science-Economics) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: Social Networking